Anomie, irritation, and happiness in the Chilean society post-social outbreak - Moyano-Díaz, Emilio; Palomo-Vélez, Gonzalo; Olivos-Jara, Pablo; Maya-López, Yuxa (Frontiers in Psychology, 2023)
On October 18, 2019, the Chilean people witnessed an unprecedented social upheaval in most of the country. We believe that it is one more manifestation -the most acute by the way- of a prolonged period of anomie that in turn feeds back on itself. We argue here that a state of anomie could negatively influence people's well-being through a greater feeling of irritation. Convenience recruitment via social networks allowed us to form a sample of 194 Chilean participants from the center-south region of the country (M = 36.53 years old, SD = 17.48; 56.7% women). All participants completed instruments to measure anomie, irritation, happiness and political beliefs. Descriptive scores situated Chile in the quadrant of high anomie. Two mediation analyses were conducted. The main results showed a negative indirect effect of the breakdown of the social fabric and leadership on happiness through irritation, although the findings for the former dimension were more robust. Additionally, the breakdown of the social fabric was positively related to the belief that left and right-wing democratic governments are helpless when it comes to fighting delinquency. The breakdown of leadership, on the other hand, was negatively related to political interest. The results reveal the important role of political irritation as a mediator of the effects of anomie on the happiness of citizens. Keywords: anomie, social outbreak, political irritation, happiness.